C-19 and Hot, Wide Star Streams - Raymond G. Carlberg; Rodrigo Ibata; Nicolas F. Martin; Else Starkenburg; David S. Aguado; Khyati Malhan; Kim Venn; Zhen Yuan (The Astrophysical Journal, 2025)
The C-19 star stream has the abundance characteristics of an unusually metal-poor globular cluster but kinematically is uncharacteristically hot and wide for a cluster stream, having a line-of-sight velocity dispersion of 7  ±  2 km s ^−1 and a 1 σ width of 240 pc. We show that the tidal dissolution of an old, lower-mass globular cluster in a cold dark matter (CDM) galactic halo can create a hot, wide stream currently near orbital apocenter. A cosmological Milky Way n -body simulation motivates the parameters for an evolving Milky Way halo potential containing an orbiting subhalo population in which we model a star cluster progenitor of C-19. The same model parameters have been used for a GD-1 stream model. The ∼7 km s ^−1 velocity dispersion is readily accomplished with an evolving CDM subhalo population, a progenitor cluster mass ≃2 × 10 ^4 M _⊙ , and an orbit that keeps the progenitor orbital pericenter within about 10 kpc of the Milky Way dark halo or its precursors.